An original risk score to predict early major bleeding in acute pulmonary embolism: the Syncope, Anemia, Renal Dysfunction (PE-SARD) bleeding score. (14th October 2021) - Chopard, R; Piazza, G; Falvo, N; Ecarnot, F; Besutti, M; Capellier, G; Schiele, F; Badoz, M; Meneveau, N
Abstract: Background: Improved prediction of the risk of early major bleeding in pulmonary embolism (PE) is needed to optimize acute management. Methods: Using data from a multicenter prospective registry including 2, 754 patients, we performed multivariable logistic regression analysis to build a risk score to predict early (up to hospital discharge) major bleeding events. We validated the endpoint model internally using bootstrapping in the derivation dataset by sampling with replacement for 500 iterations. We compared the performance of this novel score to that of the VTE-BLEED and RIETE models. Results: Multivariate regression identified three predictors for the occurrence of 82 major bleeds (3.0%): Syncope (+1.5 points), Anemia defined by a hemoglobin level <12 g/dL (+2.5 points), and Renal Dysfunction defined by a glomerular filtration rate <60 mL/min (+1 point). The PE-SARD bleeding score was calculated by summing all the components. Overall, 52.2% of patients were classified as low bleeding-risk (score, 0 point), 35.2% intermediate-risk (score, 1–2.5 points), and 12.6% high-risk (score >2.5 points). Cumulative observed bleeding rates increased with increasing risk group, from 0.9% in the low-risk group to 9.0% in the high-risk group. The C-index was 0.744 (95% CI, 0.73–0.76) and Brier score 0.028 in the derivation cohort. Similar values were calculated from internal bootstrapping. Performance of the PE-SARD score was better than that observed with the VTE-BLEED and RIETE scores (figure). Conclusions: The PE-SARD bleeding risk score is an original, user-friendly score to estimate the risk of early major bleeding in patients with acute PE. FUNDunding Acknowledgement: Type of funding sources: None.